Collateral Ownership as A Stepping Stone to Formal Credit Accessibility: A Perspective of Cottage Industry Owners (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The study investigates the influence of collateral ownership on formal credit accessibility for cottage industry owners in Dodoma, Tanzania.Design/Methodology/Approach: A cross-sectional survey randomly sampled 357 cottage industry owners from Dodoma City and Chamwino District Council in the Dodoma Region. Quantitative and qualitative data collection methods were used, including surveys and interviews. The analysis employed SPSS software to perform descriptive and inferential statistics, including Chi-square tests and binary logistic regression, to examine the influence of collateral ownership and formal credit accessibility.Findings: The study found that most cottage industry owners with collateral can only access a small amount of formal credit of up to five million Tanzanian shillings. Similarly, the study revealed that ownership of tangible assets, title deeds, business assets, and employment contracts significantly enhances the likelihood of cottage industry owners accessing credit from formal financial institutions in Dodoma, Tanzania.Research Limitation: The study concentrated on collateral ownership and formal credit accessibility to Dodoma City and Chamwino District Council cottage industry owners. Thus, the findings may not apply to all Tanzanian cottage industry owners within the councils due to different regional administrative structures. Also, future studies can examine how interest rates, the availability of business records, and the location of the business may affect formal credit accessibility.Practical Implication: Understanding the role of collateral ownership is crucial in informing policies to improve financial inclusion and reduce poverty.Social Implication: Enhancing credit accessibility through collateral ownership to cottage industry owners can promote economic growth and job creation in Tanzania.Originality/ Value: The application of credit rationing theory in comprehending the influence of collateral ownership and credit accessibility for cottage industry owners in Tanzania, contributing to the financial ecosystem for informal businesses in developing economies.
Keywords: Accessibility. collateral ownership. cottage industry. formal credit. Tanzania